Simulation of Queue System of Retirement Fund Retrieval at The Sanggau Post Office During the Covid-19 Pandemic Using Arena Software - Yulianti Wulandari; Tri Wahyudi; Ratih Rahmahwati; Silvia Uslianti; Febri Prima (OPSI, 2021)
PT. Pos Indonesia (Persero) entered into a collaboration with PT. Taspen (Persero) in the payment of pension funds. The Sanggau Post Office is a place of public service, where during the Covid-19 pandemic there were still many people queuing to collect pension funds. The number of customers who took pension funds was 208 customers, so there was a long queue which resulted in the crowds of customers queuing up. The application of physical distancing as an effort to prevent the spread of Covid-19 by implementing health protocols while queuing. According to WHO, the physical distancing distance is one to two meters. The need to reduce the queues that occurred during the Covid-19 pandemic can be designed a queuing system model in accordance with existing conditions and an alternative proposed improvement for the optimal queuing system using a simulation method with the help of Arena software. The results showed that the average total time was 10.9 minutes and the average waiting time was 33.9 minutes. Based on the results of the repair scenario, the best scenario for improvement is scenario 2, in the form of a proposed improvement for the addition of 2 counters. Scenario 2 obtains an average total time of 4.9 minutes, while the average waiting time is 5.04 minutes. Therefore, the Sanggau Post Office can add 2 service counters, so there are 3 counters that can serve customers taking pension funds.